Existence theorems for some abstract nonlinear non-autonomous systems with delays - Amster, Pablo Gustavo (2014)
For some abstract classes of nonlinear non-autonomous systems with variable and state-dependent delays existence, non-existence and multiplicity of periodic solutions are discussed. To illustrate the efficiency of the method, we obtain some well-known results for applied systems as corollaries of our existence theorems.